Workforce Development Needs and Objectives of Today’s Transportation Engineering Professionals - Chang, Kevin N.; Lutz, Benjamin; Brown, Shane (Transportation research record, 2020)
Given the growing influence of technology and innovation, the skill set and knowledge required of today’s transportation engineering professional includes many different subject areas. For this reason, transportation engineers and managers alike must constantly seek out workforce development opportunities to expand either their learning or the skill set of their employees. This study examined transportation education needs from a Pacific Northwest regional perspective on two fronts. First, an assessment was initiated identifying available course training offerings and their curriculum and delivery characteristics. Second, an investigation into training needs was conducted using a mixed-method approach consisting of personal interviews and an online survey. This study concluded that although training is a highly personal decision and influenced by many different factors, those related to cost, location, and topic area ultimately drive an individual or agency to pursue such opportunities. These findings can inform both practitioners and researchers to strategically determine how future training opportunities should be developed and shaped to meet the growing demands of tomorrow’s transportation engineer.